Penanganan Perkara Tindakan Faktual Pemerintah Sebagai Objek Sengketa di Pengadilan Tata Usaha Negara - Rismahayani, Dewa Ayu Made Vidya; Bela Siki Layang, I Wayan (Kertha Patrika; Vol 46 No 3 (2024), 2024)
The establishment of the State Administrative Court essentially intends to safeguard the citizens' fundamental rights regarding legal certainty in pursuing justice, particularly people affected by government actions. The purpose of this study is to determine the meaning of factual government actions as objects of dispute and analyze the handling of cases in the State Administrative Court. This normative legal studies applies statutory and conceptual approaches. The result of this research is that the application of the government administration law accommodates Factual Actions as state administrative decisions. The expansion gives broader authority to the State Administrative Court to handle the settlement of Factual Action cases, so that a suit against unlawful acts can be filed to declare that the government's factual actions are in contradiction with the law, and it is permitted to claim compensation if the decision can be understood as a Factual Action in accordance to Article 87 letter a of the Government Administration Law and the compensation application refers to Article 53 paragraph (1) of the State Administrative Court Law.